Analisis Pertumbuhan Bibit Bakau Rhizophora stylosa Griff. di Kawasan Rehabilitasi Mangrove Tanjung Pasir, Tangerang - Pramudji; Wayan Eka Dharmawan, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Growth Analysis of Rhizophora stylosa Griff. Seedlings in Mangrove Rehabilitation Area of Tanjung Pasir, Tangerang. Mangrove rehabilitation is urgently needed as an effort to preserve coastal plant ecosystems which are decreasing in Indonesia. It requires the preparation of good seedlings to support the rehabilitation efforts. The seedling of Rhizophora stylosa is suitable for being able to well adapt to the wide range of salinity and illumination. Research on the growth of R. stylosa seedlings was conducted in degraded mangrove areas in the coastal region of Tanjung Pasir, Tangerang, from August to November 2005. This research analyzes the growth patterns R. stylosa seedlings in two habitat types, i.e. the pond dikes and the green belts. A total of 100 seedlings were planted in each habitat with a spacing of 0.5 m. Seedling growth parameters such as the percentage of survival, height and diameter of the stem, and number of leaves were measured monthly. Twoway ANOVA analysis was conducted to determine the overall differences in the parameters between locations and time of observation, as well as its interaction. The results showed the percentage of survival of seedlings planted in the green belts was higher than in the pond dikes (p <0.05), while the growth of the height and diameter of the seedlings planted in the pond dikes was higher than those planted in the green belts. The number of leaves of seedlings planted in both habitats was not significantly different. The regression equation between seedling height (X) and stem diameter (Y) showed a high correlation (p <0.01) in the green belts, which is Y = 0,018X + 0.746 (R = 0.606). A strong correlation was found between stem height (X) and the number of leaves (Y) for the seedlings planted in the pond dikes by the regression equation Y = 0,156X - 2.968 (R = 0.501).